Sõja mõju tsiviilelanikkonnale keskaegse Liivimaa konfliktides [Non-military population in war: the case of medieval Livonia] - Lätte, Mart (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
According to the battle-centred doctrines of the war theorist Karl von Clausewitz, historians were for a long time on the opinion that medieval warfare, which did not involve a striking number of battles, was nothing but uncoordinated and pointless pillage. The view began to change in the second half of the 20th century mostly due to the works of Jan Frans Verbruggenand Philippe Contamine.In fact, medieval warfare was very thoroughly-planned and the warof pillage had its own specific purposes. Unlike the times of Clausewitz,when the purpose of warfare was to gain victory by destroying the enemy army in battle, in the Middle Ages, battles were avoided and belligerents tried to force the opponent to surrender in other ways. The destroying of the economic potential and the population of the opponent by pillagingand killing played an important part in the process. Thus, it can be said that warfare was directed against that part of the society nowadays known as the civilian population.(Longer version of the current abstract is included in the article, starting from p 30.)